Syn-eruptive hydrothermal degassing and CO2 fluxes at the Planchón-Peteroa Volcanic complex (Chile-Argentina): evidence from dissolved gases, isotopes, and radon tracers - L. Ruggiero; A. Sciarra; N. Vigide; M.C. Tartarello; H. Barcelona; R. Maffucci; A. Conti; G. Galli; S. Bigi (Journal of Volcanology and Geothermal Research, 2026)

A coupled geotechnical and sediment transport model to predict dune erosion during storms - S. Conti; I.L. Turner; K.D. Splinter (Coastal Engineering, 2026)

Biosurfactants from marine thermophilic bacilli for mitigating soil dehydration and preventing plant diseases - V. Zammuto; A. Macrì; M. T. Caccamo; S. Magazù; E. Conti; D. Leone; A. Spanò; C. Gugliandolo (International Journal of Environmental Science and Technology, 2026)

Unveiling “Mid-Pliocene Warm Period” dynamics through multiproxy stratigraphic analysis: The Valdelsa Basin in Northern Apennines – Italy as a key archive - L. Milaneschi; G. Cornamusini; P. Conti; I. Martini; J. Maffei; F. Cifelli; M. Mattei; S. Da Prato; M.C. Alçiçek; L.M. Foresi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

Corrigendum to “Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets” [Applied Soil Ecology 204 (2024) 105710] - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2026)

Exploring light-effects of microalgal extract on zebrafish caudal fin cell regeneration for aquaculture applications - F. Conti; E. Frigato; E. Ruohisto; J. F. López-Olmeda; F. J. Sánchez-Vázquez; C. Baldisserotto; C. Bertolucci; S. Pancaldi (Aquaculture International, 2026)

The daily rhythms of temperature preference are conserved in nocturnal and blind fish - F. Conti; E. Gatto; G. de Alba; S. Pintos; J.F. López-Olmeda; L.M. Vera; S. Rey Planellas; S.A. Mackenzie; C. Bertolucci; F.J. Sánchez-Vázquez (Journal of Thermal Biology, 2025)

Extracellular vesicle-associated miR-222-3P and miR-186-5P as hypoxic markers in canine osteosarcoma: An in vitro study - R. De Maria; L. Maniscalco; M. Poncina; S. Divari; L. Parisi; S. Sonia; L. Cesar Conti; E. Mazzone; L. Aresu (Journal of Comparative Pathology, 2025)

Immunohistochemical profiling of B7-H3 expression in canine solid and liquid neoplasms - L. Cesar Conti; S. Capellero; S. Divari; L. Maniscalco; E. Mazzone; M. Olimpo; L. Aresu; R. De Maria (Journal of Comparative Pathology, 2025)

Short-chain per- and polyfluoroalkyl substances associate with elevated alanine aminotransferase: Cross-sectional analysis results from the STRIVE cohort - Bojung Seo; Hongxu Wang; Rachel Maguire; Yukun Liu; Beatrice Smith; Kristin Haller; Marjorie Riggan; David V. Conti; Heinz-Josef Lenz; Kara Wegermann; Antonio Planchart; Giorgio Roccaro; et al. (Environmental Research, 2025)

Immunization of rabbits with nanovenom composed of Dendroaspis polylepis venom and silica nanoparticles: a first in vivo approach - Federico G. Baudou; María Herrera; Mariángela Vargas; Mauren Villalta; Florencia S. Conti; Exequiel Giorgi; Laura Leiva; José María Gutiérrez; Adolfo R. de Roodt; Mauricio de Marzi (Toxicon, 2025)

Evaluating 3D-Printed Pre-separator Inserts in a Fast Screening Impactor for Physicochemical Characterization of Fine Particle Dose Release from Dry Powder Inhalers - Nathan A. Reed; Roee Dar; Nicholas Holtgrewe; Leo N. Y. Cao; Xiaofei Liu; Denise S. Conti; Bryan Newman; Elizabeth Bielski; Jason D. Rodriguez; Changning Guo (AAPS PharmSciTech, 2025)

Isolation of a novel microplastic-degrading bacterial strain: a promising agent for low-density polyethylene remediation - S.B. Cabigliera; D. Gaudioso; D. Chelazzi; L. Conti; B. Muzzi; D. Cantagalli; A. Cincinelli; S. Tegli; A. Jenkins; T. Martellini (Chemosphere, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Edaphobase 2.0: Advanced international data warehouse for collating and using soil biodiversity datasets - D.J. Russell; E. Naudts; N.A. Soudzilovskaia; M.J.I. Briones; M. Çakır; E. Conti; J. Cortet; C. Fiera; D. Hackenberger Kutuzovic; M. Hedde; K. Hohberg; D. Indjic; et al. (Applied Soil Ecology, 2024)

Observations on the role of internal sand moisture dynamics in wave-driven dune face erosion - S. Conti; K.D. Splinter; E. Booth; D. Djadjiguna; I.L. Turner (Geomorphology, 2024)

Microstructural Characterization of Dry Powder Inhaler Formulations Using Orthogonal Analytical Techniques - Gonçalo Farias; William J. Ganley; Robert Price; Denise S. Conti; Sharad Mangal; Elizabeth Bielski; Bryan Newman; Jagdeep Shur (Pharmaceutical Research, 2024)
Purpose For locally-acting dry powder inhalers (DPIs), developing novel analytical tools that are able to evaluate the state of aggregation may provide a better understanding of the impact of material properties and processing parameters on the in vivo performance. This study explored the utility of the Morphologically-Directed Raman Spectroscopy (MDRS) and dissolution as orthogonal techniques to assess microstructural equivalence of the aerosolized dose of DPIs collected with an aerosol collection device. Methods Commercial DPIs containing different strengths of Fluticasone Propionate (FP) and Salmeterol Xinafoate (SX) as monotherapy and combination products were sourced from different regions. These inhalers were compared with aerodynamic particle size distribution (APSD), dissolution, and MDRS studies. Results APSD testing alone might not be able to explain differences reported elsewhere in in vivo studies of commercial FP/SX drug products with different Advair® strengths and/or batches. Dissolution studies demonstrated different dissolution rates between Seretide™ 100/50 and Advair® 100/50, whereas Flixotide™ 100 and Flovent® 100 had similar dissolution rates between each other. These differences in dissolution profiles were supported by MDRS results: the dissolution rate is increased if the fraction of FP associated with high soluble components is increased. Principle component analysis was used to identify the agglomerate classes that better discriminate different products. Conclusions MDRS and dissolution studies of the aerosolized dose of DPIs were successfully used as orthogonal techniques. This study highlights the importance of further assessing in vitro tools that are able to provide a bridge between material attributes or process parameters and in vivo performance.

P13-17 Assessment of the efficiency of the literature search of the ten key characteristics of carcinogens in the IARC Monographs evaluation process - C. Facchin; A. De Conti; L. Benbrahim-Tallaa; S. Chittiboyina; S. Ruiz; M. Schubauer-Berigan; F. Madia (Toxicology Letters, 2024)

Effect of different deficit irrigation regimes on vine performance, grape composition and wine quality of the “Primitivo” variety under mediterranean conditions - P. Losciale; L. Conti; S. Seripierri; V. Alba; F. Mazzone; L. Rustioni; G. di Leo; F. Tarricone; L. Tarricone (Irrigation Science, 2024)
Climate change represents one of the current major challenges and the improper use of water resources is an impeding threat. Agricultural research can play a crucial role by developing innovative strategies and techniques to reduce water use without affecting crop productivity and quality, particularly in grapevine growing in Mediterranean areas, as both productivity and wine quality are quintessential for the economic and ecologic sustainability of this crop. The present study aimed to define a deficit irrigation strategy for the “Primitivo” grapevine cultivar, taking into account the overall pathway of the vineyard performance in terms of leaf functionality, starch reserves, vine productivity, and wine quality. The trial was carried out in Southern-Italy on a three year-old, drip irrigated vineyard, imposing four deficit irrigation regimes for two consecutive seasons, consisting of 29 (T29), 55 (T55), 85 (T85) and 100% (T100) of crop evapotranspiration (ET C ). Mild water restriction (T85) did not affect vegetative nor reproductive vine performance. Deficit irrigation at 55% ET C lowered leaf functionality, starch accumulation, vine vigour and yield, due to a reduction of cluster weight; however, wine acidity and phenolic compounds were increased. T29 further decreased yield, as also the number of clusters was reduced. The most water-stressed treatment revealed a low concentration of malic acid in the must and a consequent increase of the ethanol sensation in the wine. After 9 months ageing, T85 had the highest wine colour intensity suggesting this treatment as the most promising in terms of quality and quantity of wine as well as for water saving.

Biogeography of orchids and their pollination syndromes in small Mediterranean islands - M. Lussu; P. Zannini; R. Testolin; D. Dolci; M. Conti; S. Martellos; A. Chiarucci (Journal of Biogeography, 2024)
Aims Despite the research on orchid in insular conditions, few studies are focused on the spatial distribution of their reproductive syndromes across complex insular systems. By using island species–area relationships (ISAR), we explore orchid biogeography in the Central Western‐Mediterranean islands. In this study, we aim to investigate variation in ISARs using orchid pollination mechanisms as proxies to establish permanent populations explaining how the c and z parameters of ISARs vary among island types and pollination strategies and defining the most influential factors in shaping orchids' distribution. Location Mediterranean Basin. Taxon Orchidaceae. Methods Checklist of native orchids was obtained for 112 islands of Central‐Western Mediterranean Basin. The Arrhenius power function () was used to fit ISARs for the total number of orchids as well as for functional groups defined by the pollination strategies, across different island types. We used GLM to investigate the relation between pollination syndromes with area and isolation as well as elevation, island origin, taxa richness of the source area and habitat diversity. Results We found that ISARs differ between continental and volcanic islands depending on isolation. The z ‐value was found to be higher for more specialized strategies while the c ‐value increases from autogamy to allogamy, supporting the role of these two parameters in understanding distributional dynamics. Distance from the mainland is a negative predictor for all the strategies except when deception is decoupled; island area is a positive predictor only for allogamic, deceptive and food deceptive strategies, while habitat diversity is a positive predictor for allogamic, rewarding and deceptive strategies. Main Conclusions Pollination syndromes contribute in explaining the distribution of orchids in insular conditions. Furthermore, we identified differences in ISARs across pollination syndromes in which the intercept increases when the pollination shifts from a generalist to a more specialized one.

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

The transition from normal marine to evaporitic conditions recorded in a cold seep environment: The Messinian succession of Northern Italy - S. Conti; C. Argentino; M. Bojanowski; C. Fioroni; S. Giunti; B. Kremer; D. Fontana (Marine and Petroleum Geology, 2024)

New olive-pomace fertilizer tested with a 2-tiers approach: Biomarkers on Eisenia fetida, physiochemical effects on Solanum lycopersicum and Olea europaea - S. Parri; T. Campani; V. Conti; G. Cai; M. Romi; S. Casini; R. Zari; F. Caldini; L. Marsili (Journal of Environmental Management, 2024)

Investigating the potential of African land snail shells (Gastropoda: Achatininae) for amino acid geochronology - Chloë Baldreki; Andrew Burnham; Martina Conti; Lucy Wheeler; Michael J. Simms; Lawrence Barham; Tom S. White; Kirsty Penkman (Quaternary Geochronology, 2024)

Understanding the Ultra-Rare Disease Autosomal Dominant Leukodystrophy: an Updated Review on Morpho-Functional Alterations Found in Experimental Models - Irene Neri; Giulia Ramazzotti; Sara Mongiorgi; Isabella Rusciano; Marianna Bugiani; Luciano Conti; Margot Cousin; Elisa Giorgio; Quasar S. Padiath; Giovanna Vaula; Pietro Cortelli; Lucia Manzoli; et al. (Molecular Neurobiology, 2023)
Autosomal dominant leukodystrophy (ADLD) is an ultra-rare, slowly progressive, and fatal neurodegenerative disorder associated with the loss of white matter in the central nervous system (CNS). Several years after its first clinical description, ADLD was found to be caused by coding and non-coding variants in the LMNB1 gene that cause its overexpression in at least the brain of patients. LMNB1 encodes for Lamin B1, a protein of the nuclear lamina. Lamin B1 regulates many cellular processes such as DNA replication, chromatin organization, and senescence. However, its functions have not been fully characterized yet. Nevertheless, Lamin B1 together with the other lamins that constitute the nuclear lamina has firstly the key role of maintaining the nuclear structure. Being the nucleus a dynamic system subject to both biochemical and mechanical regulation, it is conceivable that changes to its structural homeostasis might translate into functional alterations. Under this light, this review aims at describing the pieces of evidence that to date have been obtained regarding the effects of LMNB1 overexpression on cellular morphology and functionality. Moreover, we suggest that further investigation on ADLD morpho-functional consequences is essential to better understand this complex disease and, possibly, other neurological disorders affecting CNS myelination. Graphical Abstract

Metronidazole Degradation by Physico-chemical and Advanced Oxidative Processes: Influence of pH and nTiO2-Functionalized Macroporous Support - Eric Sanches-Simões; Renan C. Testolin; Felipe M. Müller; Otto M. S. Gerlach; Wendell Pimentel-Almeida; Aline Dal Conti-Lampert; Albertina X. R. Corrêa; Gizelle I. Almerindo; Sergio Y. Gómez González; Claudemir M. Radetski (Water, Air, & Soil Pollution, 2022)

Systematic Evaluation of the Effect of Formulation Variables on In Vitro Performance of Mometasone Furoate Suspension-Metered Dose Inhalers - Sagar S. Bachhav; Poonam Sheth; Dennis Sandell; Mårten Svensson; Sharvari Bhagwat; Denise S. Conti; Oluwamurewa Oguntimein; Sneha Dhapare; Bhawana Saluja; Lawrence Winner; Jürgen B. Bulitta; Guenther Hochhaus (The AAPS Journal, 2022)

Correction to: Can Pharmacokinetic Studies Assess the Pulmonary Fate of Dry Powder Inhaler Formulations of Fluticasone Propionate? - Günther Hochhaus; Mong-Jen Chen; Abhinav Kurumaddali; Uta Schilling; Yuanyuan Jiao; Stefanie K. Drescher; Elham Amini; Simon M. Berger; Bhargava Kandala; Christine Tabulov; Jie Shao; Brandon Seay; et al. (The AAPS Journal, 2022)

Can Pharmacokinetic Studies Assess the Pulmonary Fate of Dry Powder Inhaler Formulations of Fluticasone Propionate? - Günther Hochhaus; Mong-Jen Chen; Abhinav Kurumaddali; Uta Schilling; Yuanyuan Jiao; Stefanie K. Drescher; Elham Amini; Simon M. Berger; Bhargava Kandala; Christine Tabulov; Jie Shao; Brandon Seay; et al. (The AAPS Journal, 2021)

Correction to: Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Preservation of 34S-enriched sulfides in fossil sulfate-methane transition zones: new evidence from Miocene outcrops of the northern Apennines (Italy) - C. Argentino; J. E. Johnson; S. Conti; C. Fioroni; D. Fontana (Geo-Marine Letters, 2020)

Infectious mononucleosis, immune genotypes, and non-Hodgkin lymphoma (NHL): an InterLymph Consortium study - Niquelle Brown Wadé; Cindy M. Chang; David Conti; Joshua Millstein; Christine Skibola; Alexandra Nieters; Sophia S. Wang; Silvia De Sanjose; Eleanor Kane; John J. Spinelli; Paige Bracci; Yawei Zhang; et al. (Cancer Causes & Control, 2020)

Development of an Aerosol Dose Collection Apparatus for In Vitro Dissolution Measurements of Orally Inhaled Drug Products - Robert Price; Jagdeep Shur; William Ganley; Gonçalo Farias; Nikoletta Fotaki; Denise S. Conti; Renishkumar Delvadia; Mohammad Absar; Bhawana Saluja; Sau Lee (The AAPS Journal, 2020)
The aim of the study was to develop a robust and standardized in vitro dissolution methodology for orally inhaled drug products (OIDPs). An aerosol dose collection (ADC) system was designed to uniformly deposit the whole impactor stage mass (ISM) over a large filter area for dissolution testing. All dissolution tests were performed under sink conditions in a sodium phosphate buffered saline solution containing 0.2% w /w sodium dodecyl sulphate. An adapted USP Apparatus V, Paddle over Disk (POD), was used throughout the study. The dissolution characteristics of the ISM dose of a commercial metered-dose inhaler (MDI) and a range of dry powder inhaler (DPI) formulations containing inhaled corticosteroids were tested. The uniform distribution of the validated ISM dose considerably reduced drug loading effects on the dissolution profiles for both MDI and DPI formulations. The improvement in the robustness and discriminatory capability of the technique enabled characterization of dissolution rate differences between inhaler platforms and between different DPI product strengths containing fluticasone propionate. A good correlation between in vivo mean absorption time and in vitro dissolution half-life was found for a range of the inhaled corticosteroids. The ADC system and the reproducible in vitro POD dissolution measurements provided a quantitative-based approach for measuring the relationship between the influence of device and the dispersion characteristics on the aerosol dissolution of low solubility compounds. The in vitro dissolution method could potentially be applied as a dissolution methodology for compendial, quality control release testing, and during development of both branded orally inhaled drug products and their generic counterparts.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Developing allometric models to predict the individual aboveground biomass of shrubs worldwide - G. Conti; L. D. Gorné; S. R. Zeballos; M. L. Lipoma; G. Gatica; E. Kowaljow; J. I. Whitworth‐Hulse; A. Cuchietti; M. Poca; S. Pestoni; P. M. Fernandes (Global Ecology and Biogeography, 2019)
Aim Existing global models to predict standing biomass are based on trees characterized by a single principal stem, well developed in height. However, their use in open woodlands and shrublands, characterized by multistemmed species with substantial crown development, generates a high level of uncertainty in biomass estimates. This limitation led us to (a) develop global models of shrub individual aboveground biomass based on simple allometric variables, (b) to compare the fit of these models with existing global biomass models, and (c) to assess whether models fit change when bioclimatic variables are considered. Location Global. Time period Present. Major taxa studied 118 species of shrubs. Methods We compile a database of 3,243 individuals across 49 sites distributed worldwide. Including stem basal diameter, height and crown diameter as predictor variables, we built potential models and compared their fit using generalized least squares. We used mixed effects models to determine if bioclimatic variables improved the accuracy of biomass models. Results Although the most important variable in terms of predictive capacity was stem basal diameter, crown diameter significantly improved the models’ fit, followed by height. Four models were finally chosen, with the best model combining all these variables in the same equation [ R 2 = 0.930, root mean square error (RMSE) = 0.476]. Selected models performed as well as established global biomass models. Including the individual bioform significantly improved the models’ fit. Main conclusions Stem basal diameter, crown diameter and height measures could be combined to provide robust aboveground biomass (AGB) estimates of individual shrub species. Our study supplements well‐established models developed for trees, allowing more accurate biomass estimation of multistemmed woody individuals. We further provide tools for a methodological standardization of individual biomass quantification in these species. We expect these results contribute to improve the quality of biomass estimates across ecosystems, but also to generate methodological consensus on field biomass assessments in shrubs.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Microparticles and autophagy: a new frontier in the understanding of atherosclerosis in rheumatoid arthritis - C. Barbati; M. Vomero; T. Colasanti; F. Ceccarelli; M. Marcosano; F. Miranda; L. Novelli; A. Pecani; Carlo Perricone; F. R. Spinelli; S. Truglia; F. Conti; et al. (Immunologic Research, 2018)

Effects of Formulation Variables on Lung Dosimetry of Albuterol Sulfate Suspension and Beclomethasone Dipropionate Solution Metered Dose Inhalers - Jeffry D. Schroeter; Poonam Sheth; Anthony J. Hickey; Bahman Asgharian; Owen T. Price; Jay T. Holt; Denise S. Conti; Bhawana Saluja (AAPS PharmSciTech, 2018)

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Influence of Formulation Factors on the Aerosol Performance of Suspension and Solution Metered Dose Inhalers: A Systematic Approach - Poonam Sheth; Dennis Sandell; Denise S. Conti; Jay T. Holt; Anthony J. Hickey; Bhawana Saluja (The AAPS Journal, 2017)

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

Altered soil carbon dynamics under different land-use regimes in subtropical seasonally-dry forests of central Argentina - G. Conti; E. Kowaljow; F. Baptist; C. Rumpel; A. Cuchietti; N. Pérez Harguindeguy; S. Díaz (Plant and Soil, 2016)

Optical Characterization of Normal, Benign, and Malignant Thyroid Tissue: A Pilot Study - M. P. Brandao; R. Iwakura; F. S. Basilio; K. Haleplian; A. S. Ito; L. C. Conti de Freitas; L. Bachmann (Journal of Fluorescence, 2015)

Erratum to: Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Copper availability assessment of Cu-contaminated vineyard soils using black oat cultivation and chemical extractants - Eduardo Girotto; Carlos A. Ceretta; Gustavo Brunetto; Alcione Miotto; Tadeu L. Tiecher; Lessandro De Conti; Cledimar R. Lourenzi; Felipe Lorensini; Paulo I. Gubiani; Leandro S. da Silva; Fernando T. Nicoloso (Environmental Monitoring and Assessment, 2014)

Topo‐climatic microrefugia explain the persistence of a rare endemic plant in the Alps during the last 21 millennia - Theofania S. Patsiou; Elena Conti; Niklaus E. Zimmermann; Spyros Theodoridis; Christophe F. Randin (Global Change Biology, 2014)
Ongoing rapid climate change is predicted to cause local extinction of plant species in mountain regions. However, some plant species could have persisted during Quaternary climate oscillations without shifting their range, despite the limited evidence from fossils. Here, we tested two candidate mechanisms of persistence by comparing the macrorefugia and microrefugia ( MR ) hypotheses. We used the rare and endemic Saxifraga florulenta as a model taxon and combined ensembles of species distribution models ( SDM s) with a high‐resolution paleoclimatic and topographic dataset to reconstruct its potential current and past distribution since the last glacial maximum. To test the macrorefugia hypothesis, we verified whether the species could have persisted in or shifted to geographic areas defined by its realized niche. We then identified potential MR based on climatic and topographic properties of the landscape and applied refined scenarios of MR dynamics and functions over time. Last, we quantified the number of known occurrences that could be explained by either the macrorefugia or MR model. A consensus of two or three SDM techniques predicted absence between 14–10, 3–4 and 1 ka bp , which did not support the macrorefugia model. In contrast, we showed that S. florulenta could have contracted into MR during periods of absence predicted by the SDM s and later re‐colonized suitable areas according to the macrorefugia model. Assuming a limited and realistic seed dispersal distance for our species, we explained a large number of the current occurrences (61–96%). Additionally, we showed that MR could have facilitated range expansions or shifts of S. florulenta . Finally, we found that the most recent and the most stable MR were the ones closest to current occurrences. Hence, we propose a novel paradigm to explain plant persistence by highlighting the importance of supporting functions of MR when forecasting the fate of plant species under climate change.

Polymeric Nanocarriers for Transport Modulation across the Pulmonary Epithelium: Dendrimers, Polymeric Nanoparticles, and their Nanoblends - Balaji Bharatwaj; Radovan Dimovski; Denise S. Conti; Sandro R. P. da Rocha (The AAPS Journal, 2014)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Distribution range and ecological niche of Primula marginata Curtis (Primulaceae) - G. Casazza; S. Marsili; L. Granato; E. Conti; V. Noble; A. Selvaggi; L. Minuto (Plant Biosystems, 2013)

An integrated GIS for sedimentological and geomorphological analysis of a lagoon environment. Barra de Cananéia inlet region, (Southeastern Brazil) - Luis Américo Conti; Carlos Alberto S. Araujo; Fernando S. Paolo; Roberto L. Barcellos; Marcelo Rodrigues; Michel M. Mahiques; Valdenir V. Furtado (Journal of Coastal Conservation, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

Clinical findings and diagnosis in a case of cholangiocellular carcinoma in a horse - M. B. Conti; M. C. Marchesi; F. Zappulla; D. Buttarelli; E. Lepri; F. Passamonti; S. Galletti; G. Rucco; F. Rueca (Veterinary Research Communications, 2008)

Equine adipose-tissue derived mesenchymal stem cells and platelet concentrates: their association in vitro and in vivo - M. Del Bue; S. Riccò; R. Ramoni; V. Conti; G. Gnudi; S. Grolli (Veterinary Research Communications, 2008)

Platelet Lysate Promotes in Vitro Proliferation of Equine Mesenchymal Stem Cells and Tenocytes - M. Del Bue; S. Riccò; V. Conti; E. Merli; R. Ramoni; S. Grolli (Veterinary Research Communications, 2007)

Chronic administration of olanzapine induces metabolic and food intake alterations: a mouse model of the atypical antipsychotic-associated adverse effects - R. Coccurello; A. Caprioli; O. Ghirardi; R. Conti; B. Ciani; S. Daniele; A. Bartolomucci; A. Moles (Psychopharmacology, 2006)

Thrusting and faulting in metamorphic and sedimentary units of Ligurian Alps: an example of integrated field work and geochemical analyses - F. Piana; S. Tallone; S. Cavagna; A. Conti (International Journal of Earth Sciences, 2006)

Diet and cooling interactions on physiological responses of grazing dairy cows, milk production and composition - M. R. Gallardo; S. E. Valtorta; P. E. Leva; M. C. Gaggiotti; G. A. Conti; R. F. Gregoret (International Journal of Biometeorology, 2005)

Chemical Cues from Murgantia histrionica Eliciting Host Location and Recognition in the Egg Parasitoid Trissolcus brochymenae - Eric Conti; Gianandrea Salerno; Ferdinando Bin; Howard J. Williams; S. Bradleigh Vinson (Journal of Chemical Ecology, 2003)

Genetic Analysis of Neoplasia Induced by N-Nitroso-N-methylurea in Xiphophorus Hybrid Fish - Steven Kazianis; Irma Gimenez-Conti; David Trono; Anthony Pedroza; Lori B. Chovanec; Donald C. Morizot; Rodney S. Nairn; Ronald B. Walter (Marine Biotechnology, 2001)

A Proposed Classification Scheme for Xiphophorus Melanomas Based on Histopathologic Analyses - Steven Kazianis; Richard B. Setlow; John C. Harshbarger; Arvil D. Woodhead; Ronald B. Walter; Rodney S. Nairn; Irma Gimenez-Conti (Marine Biotechnology, 2001)

Generation of TNFα, IFNγ, IL-4, IL-6 and IL-10 in Trichinella spiralis infected mice: effect of the anti-inflammatory compound mimosine - S. Frydas; N. Papaioannou; M. Hatzistilianou; D. Merlitti; M. Di Gioacchino; M.L. Castellani; P. Conti (Inflammopharmacology, 2001)

Geochemical changes at the Bagni di Triponzo thermal spring during the Umbria-Marche 1997–1998 seismic sequence - F. Quattrocchi; R. Pik; L. Pizzino; M. Guerra; P. Scarlato; M. Angelone; M. Barbieri; A. Conti; B. Marty; E. Sacchi; G.M. Zuppi; S. Lombardi (Journal of Seismology, 2000)

In situ X-ray absorption spectroelectrochemical study of hydroxocobalamin - M. Giorgetti; I. Ascone; M. Berrettoni; P. Conti; S. Zamponi; R. Marassi (JBIC Journal of Biological Inorganic Chemistry, 2000)

Vitamin B6-deficient diet plus 4-deoxypyridoxine (4-DPD) reduces the inflammatory response induced by T. spiralis in diaphragm, masseter and heart muscle tissue of mice - S. Frydas; N. Papaioanou; I. Vlemmas; I. Theodoridis; G. Anogiannakis; D. Vacalis; A. Trakatellis; R.C. Barbacane; M. Reale; P. Conti (Molecular and Cellular Biochemistry, 1999)

IgG, IgG1 and IgM response in Trichinella spiralis-infected mice treated with 4-deoxypirydoxine or fed a Vitamin B6-deficient diet - S. Frydas; M. Reale; D. Vacalis; R.C. Barbacane; F.C. Placido; I. Cataldo; M. Di Gioacchino; E. Karagouni; E. Dotsika; G. Anogiannakis; A. Trakatellis; P. Conti (Molecular and Cellular Biochemistry, 1999)

RFLP mapping of quantitative trait loci controlling abscisic acid concentration in leaves of drought-stressed maize (Zea mays L.) - R. Tuberosa; M. C. Sanguineti; P. Landi; S. Salvi; E. Casarini; S. Conti (Theoretical and Applied Genetics, 1998)

Induction of monocyte chemotactic protein-1 (MCP-1) and TNF alpha by Trichinella spiralis in serum of mice in vivo - M. Reale; S. Frydas; R.C. Barbacane; F.C. Placido; I. Cataldo; P. Conti; D. Vacalis; A. Trakatellis; G. Anogianakis; M. Felaco; M. Di Giocchino (Molecular and Cellular Biochemistry, 1998)

Factors influencing the expression in vitro of Candida albicans stress mannoproteins reactive with salivary secretory IgA - V. Vidotto; L. Polonelli; S. Conti; J. Pontón; I. Vieta (Mycopathologia, 1998)

Maintenance of amphetamine-induced stereotypy and locomotion requires ongoing dopamine receptor activation - Lisa H. Conti; D. S. Segal; Ronald Kuczenski (Psychopharmacology, 1997)

Protective effects of melatonin in mice infected with encephalitis viruses - D. Ben-Nathan; G. J. M. Maestroni; S. Lustig; A. Conti (Archives of Virology, 1995)

Identification of lipid components of human serum lipoproteins involved in the inhibition of Sindbis virus infectivity, hemagglutination, and hemolysis - P. Mastromarino; C. Conti; S. Rieti; N. Orsi (Archives of Virology, 1988)

Deoxyribonucleic acid base compositions of hyphomicrobia - M. Mandel; P. Hirsch; S. F. Conti (Archives of Microbiology, 1972)

Electron microscope studies on Leucothrix mucor - Thomas D. Brock; S. F. Conti (Archives of Microbiology, 1969)

Biology of budding bacteria - Peter Hirsch; S. F. Conti (Archives of Microbiology, 1964)

Biology of budding bacteria - Peter Hirsch; S. F. Conti (Archives of Microbiology, 1964)